Implementation of Law No. 13 of 2011 on the Management of the Poor in the Distribution of Social Assistance: A Siyasah Dusturiyyah Perspective - Aris Abburahman Firdaus; Bobang Noorisnan Pelita; Ridwan Eko Prasetyo (Journal of Progressive Law and Legal Studies, 2026)
Poverty as a multidimensional issue demands social assistance policies that are not only administratively effective but also substantively fair, making implementation at the local level crucial to examine. This study aims to analyze the implementation of Law Number 13 of 2011 concerning the Handling of the Poor in the distribution of social assistance in Gambarsari Village, identify the factors affecting the effectiveness of social assistance distribution, and assess its conformity with the perspective of siyasah dusturiyyah. The theoretical study focuses on the concept of public policy implementation, the validity of social welfare data, as well as the principles of trust and justice in Islamic constitutional law. The research method uses a qualitative approach with an empirical juridical method through observation, interviews, and documentation. The results of the study indicate that policy implementation has proceeded administratively, but is not yet optimal substantively. The factors that affect the effectiveness of social assistance distribution are mis-targeting, weak data validity, as well as lack of transparency and supervision. From the perspective of siyasah dusturiyyah, these conditions reflect the suboptimal implementation of the principles of justice and trustworthiness in the distribution of social assistance. The contribution of this study lies in the development of an analysis of social assistance policy implementation through the integration of positive legal approaches and the perspective of siyāsah dustūriyyah, thereby providing a conceptual contribution to strengthening social assistance governance that is more just, transparent, and oriented toward public welfare (maslahah).